Understanding quality systems in the South African prehospital emergency medical services: a multiple exploratory case study. Issue 2 (21st May 2020) - Howard, Ian; Cameron, Peter; Wallis, Lee; Castrén, Maaret; Lindström, Veronica
Abstract : Introduction: In South Africa (SA), prehospital emergency care is delivered by emergency medical services (EMS) across the country. Within these services, quality systems are in their infancy, and issues regarding transparency, reliability and contextual relevance have been cited as common concerns, exacerbated by poor communication, and ineffective leadership. As a result, we undertook a study to assess the current state of quality systems in EMS in SA, so as to determine priorities for initial focus regarding their development. Methods: A multiple exploratory case study design was used that employed the Institute for Healthcare Improvement's 18-point Quality Program Assessment Tool as both a formative assessment and semistructured interview guide using four provincial government EMS and one national private service. Results: Services generally scored higher for structure and planning. Measurement and improvement were found to be more dependent on utilisation and perceived mandate. There was a relatively strong focus on clinical quality assessment within the private service, whereas in the provincial systems, measures were exclusively restricted to call times with little focus on clinical care. Staff engagement and programme evaluation were generally among the lowest scores. A multitude of contextual factors were identified that affected the effectiveness of quality systems, centred around leadership, vision and mission, and quality system infrastructure and capacity, guided by the need for comprehensive yet pragmatic strategic policies and standards. Conclusion: Understanding and accounting for these factors will be key to ensuring both successful implementation and ongoing utilisation of healthcare quality systems in emergency care. The result will not only provide a more efficient and effective service, but also positively impact patient safety and quality of care of the services delivered.